In-silico Approach for Predicting the Inhibitory Effect of Home Remedies on Severe Acute Respiratory Syndrome Coronavirus-2 - Thapa, Shankar; Biradar, Mahalakshmi Suresha; Banerjee, Janmajoy; Karati, Dipanjan (Makara Journal of Science, 2023)
Severe Acute Respiratory Syndrome Coronavirus-2 is an infectious disease caused by coronavirus and spreads through infected droplets inhalation. For the past 3 years, COVID-19 has become a global threat. Vaccinations are currently available and have FDA approval. During the recent pandemic, people adopted a psychological belief that home remedies (turmeric, ginger, garlic, and coriander) can prevent COVID-19. This research aimed to predict the covid-19 inhibitory activities by home remedies through an in-silico approach. The 24 bioactive constituents of four home remedies plants were downloaded from PubChem and subjected to molecular docking with the three important proteins responsible for COVID-19 pathogenesis. The absorption, distribution, metabolism, and excretion (ADME) properties and toxicity of the constituents were also predicted with ADMETlab and ProTox-II software. Docking was performed with AutoDock Vina 1.5.7, and molecular interaction was visualized by Discovery studio visualizer 2021. In terms of binding energy, the active constituent present in turmeric powder (curcumin) showed the best binding interaction of ΔG = −6.8, 8.5, 8.7 kcal/mol with three different proteins Mpro (6LU7), S protein (6VXX), and ACE2 receptor protein (7P19), respectively. All the active constituents of turmeric powder have no toxicity and have suitable ADME properties. Along with curcumin and its derivatives, quercetin as an active constituent of garlic showed the best Covid-19 inhibitory effect with no toxicity. In conclusion, home remedies can prevent Covid-19 infection. In vitro animal study is required to validate these data